2012 National Turfgrass Evaluation Program Tall Fescue Test: 2012 and 2013 Data - L. Parsons; M. Kennelly; J. Griffin; J. Hoyle (Kansas Agricultural Experiment Station Research Reports, 2015)
Tall fescue is the cool-season turfgrass best adapted for the transition zone because it tolerates drought and heat and has few serious insect or disease problems. It possesses a rather coarse leaf texture, lacks stolons, and has only very short rhizomes. Efforts to improve cultivar quality include selecting for finer leaf texture, rich green color, and better sward density while maintaining good stress tolerance and disease resistance. New introductions need regular evaluation to determine their long-range suitability for use in Kansas.
Keywords: brown patch; tall fescue; turfgrass